Measuring innovation maturity – literature review on innovation maturity models - Inków, Monika (Pomiar dojrzałości innowacyjnej – przegląd literatury dotyczącej modeli dojrzałości innowacyjnej, 2019)
In recent years it has noticed that innovation and innovativeness have become the basis for the success of not only individual business entities but entire regions and economies. What is more, there have been opinions in the literature that individual innovations are no longer a guarantee of survival for an organization, but such a guarantee is rather the capacity for continuous innovation. Therefore the organization’s ability to transform resources in favour of the organization – the innovation capability – is decisive, while the ability to use resources appropriately, including innovation capabilities, is referred to as innovation maturity. In this article the author decided to introduce the essence of innovation maturity models as a tool for measuring innovation maturity. These models are a tool for assessing the level of innovation maturity of an organization. It is worth adding that maturity models originate from the Capability Maturity Model developed by the Software Engineering Institute
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 1 (51), s. 22-34
Keywords: innovation capability; innovation maturity; innovation maturity models; zdolność innowacyjna; dojrzałość innowacyjna; modele dojrzałości innowacyjnej